Thrombolysis for Evacuation of Intracerebral and Intraventricular Hemorrhage: A Guide to Surgical Protocols With Practical Lessons Learned From the MISTIE and CLEAR Trials. Issue 1 (15th December 2020) - Polster, Sean P; Carrión-Penagos, Julián; Lyne, Seán B; Goldenberg, Fernando D; Mansour, Ali; Ziai, Wendy; Carlson, Andrew P; Camarata, Paul J; Caron, Jean-Louis; Harrigan, Mark R; Gregson, Barbara; Mendelow, A David; et al.
Abstract: BACKGROUND: Minimally Invasive Surgery Plus Recombinant Tissue Plasminogen Activator for Intracerebral Hemorrhage Evacuation (MISTIE) procedure was recently tested in a large phase III randomized trial showing a significant probability of functional benefit in those cases that reached the goal hematoma evacuation of ≤15 mL residual (or ≥70% removal). Benefit of thrombolysis was also identified in cases with large intraventricular hemorrhage, and achieving at least 85% volume reduction in the Evaluating Accelerated Resolution of Intraventricular Hemorrhage (CLEAR) III trial. OBJECTIVE: To protocolize steps in the MISTIE and CLEAR procedures in order to maximize hematoma evacuation and minimize complications. METHODS: We articulate data-driven lessons and expert opinions surrounding the factors of patient selection, catheter placement, and dosing, which impacted safety and surgical performance in the MISTIE and CLEAR trials. RESULTS: Modifiable factors to maximize evacuation efficiency include optimizing catheter placement and pursuing aggressive dosing to achieve treatment goals, while strictly adhering to the safety steps as articulated in the respective trials. Prognostic factors that are viewed as nonmodifiable include greater initial intracerebral hemorrhage volume with irregular shape, smaller intraventricular bleeds, and the uncommon but consequential development of new bleeding during the dosing period despite strict protocol adherence. CONCLUSIONS: Surgeon education in this tutorial is aimed at maximizing the benefit of the MISTIE and CLEAR procedures by reviewing case selection, safety steps, treatment objectives, and technical nuances. Key lessons include stability imaging, etiology screening, and technical adherence to the protocol in order to achieve defined thresholds of evacuation.